Hydrothermal carbonization of rambutan peel (Nephelium lappaceum L.) as a Green and low-cost adsorbent for Fe(II) removal from aqueous solutions. Issue 3 (16th March 2022) - Normah, N.; Juleanti, N.; Palapa, N. R.; Taher, T.; Siregar, P. M. S. B. N.; Wijaya, A.; Lesbani, A.
ABSTRACT: This study aims to utilise rambutan peel waste and convert it into hydrochar then applied as an adsorbent to remove Fe(II) contaminants from aqueous solutions. Rambutan peel hydrochar (RP-HC) was prepared by hydrothermal treatment of raw RP at 200 °C. The prepared samples were characterised using XRD, FT-IR, BET, and SEM. The sample contains a lot of -NH and -OH active sites which will affect the performance of crude RP-HC and RP as adsorbents for the removal of Fe(II) from aqueous solutions. The results of the adsorption study showed that the adsorption of Fe(II) using RP-HC had a maximum adsorption capacity of 25.126 mg/L, while the RP was 14.553 mg/L and the adsorbent regeneration study showed that the adsorption effectiveness of RP and RP-HC was stable until the third cycle.